Understanding and Negotiating Book Publication Contracts - Schofield, Brianna; Author's Alliance; Project Muse; Project Muse. (Project Muse, 2019)
Authors are sometimes so grateful to receive a publication offer that they may be tempted to sign the first version of a publication contract that they receive, especially if negotiating seems complicated, intimidating, or risky. But there is a lot at stake for authors in a book deal, and it is well worth the effort to read the contract, understand its contents, and negotiate for favorable terms. A publication contract outlines what rights you are granting to your publisher and on what terms. If you sign away all of the rights in your book to the publisher for the life of copyright, this will preclude you from certain future uses of your work. Even if you don't have any future plans for your work, you may still regret transferring all rights if your publisher does not make full use of them, your book falls out of print, or sales drop. And the grant of rights clause is only one part of the contract that deserves your careful attention. The terms of the contract can also dictate the specifics of how you will be paid for your book, how much input you have in the appearance of your book, your commitments relating to the manuscript and future works, who is responsible for legal claims stemming from your book's content, how your book will be promoted, whether and how you can regain control over the rights to your book, and much more. Happily, authors have something of value to bring to the negotiating table (your copyrights!) and negotiation provides the opportunity to establish the terms that it works for you as well as for your publisher. Our publication contract resources empower you to understand and negotiate a publication contract that benefits you, your publisher, and readers--and ultimately increases the impact of your book.
Introduction. About this guide -- Contract basics -- Negotiation fundamentals. The grant of rights -- What rights? -- The grant of rights clause -- Subsidiary rights. Your obligations -- Your book -- Future works. Getting your book to market -- The finishing touches -- Copyright registration -- Advertising and promotion. Follow the money -- Advances -- Royalties -- accounting. Parting ways -- Assignment provisions -- Termination -- Conclusion.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Copyright -- United States -- Popular works; Authors and publishers -- United States -- Popular works; Contracts -- United States -- Popular works; Authors -- Legal status, laws, etc. -- United States -- Popular works; Electronic books